2021
DOI: 10.1007/s00170-021-07288-9
|View full text |Cite
|
Sign up to set email alerts
|

Taguchi grey relational analysis on the mechanical properties of natural hydroxyapatite: effect of sintering parameters

Abstract: Our previous study have reported synthesis and mechanical properties of natural hydroxyapatite (HA), but optimization of the measured hardness and compressive strength has not been examined. This paper presents optimization of mechanical characteristics (hardness and compressive strength), using Taguchi-grey relational analysis design. In the design, three factors with mixed levels (2 and 3) is employed with the consideration of sintering parameters (0 and 500 Pa compaction pressure, and 900, 1000 and 1100 o C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 25 publications
4
25
1
Order By: Relevance
“…Therefore, if 𝑉 𝑒 = 0.001372; 𝑓 𝑒 = 7; DOF of all the control factors is 4; R is 1; N is 36; α= 0.5 under 95% confidence interval (CI), then 𝐹 0.5 (1,7) = 5.59 based on the F-statistical table . Consequently, 𝜂 𝑒𝑓𝑓 = 36 1+4 = 7.2 and 𝐶𝐼 = √5.59 × 0.001372 [ 1 7.2 + 1 1 ] = ±0.0935. 95% of confidence interval for the optimal grey relational grade predicted is given in Equation 8 (Abifarin, 2021), The CI findings showed that the experimental GRG value of 0.6911 correlates with the predicted optimal GRG value. This affirms the efficacy of the optimal fabrication parameters on the multimechanical characteristics of kaolin reinforced hydroxyapatite.…”
Section: Confirmation Analysis 371 Confidence Interval Analysismentioning
confidence: 94%
See 3 more Smart Citations
“…Therefore, if 𝑉 𝑒 = 0.001372; 𝑓 𝑒 = 7; DOF of all the control factors is 4; R is 1; N is 36; α= 0.5 under 95% confidence interval (CI), then 𝐹 0.5 (1,7) = 5.59 based on the F-statistical table . Consequently, 𝜂 𝑒𝑓𝑓 = 36 1+4 = 7.2 and 𝐶𝐼 = √5.59 × 0.001372 [ 1 7.2 + 1 1 ] = ±0.0935. 95% of confidence interval for the optimal grey relational grade predicted is given in Equation 8 (Abifarin, 2021), The CI findings showed that the experimental GRG value of 0.6911 correlates with the predicted optimal GRG value. This affirms the efficacy of the optimal fabrication parameters on the multimechanical characteristics of kaolin reinforced hydroxyapatite.…”
Section: Confirmation Analysis 371 Confidence Interval Analysismentioning
confidence: 94%
“…The corresponding experimental hardness, compressive strength and resultant grey relational grade were analyzed using Taguchi on Minitab. The steps for generating the resultant grey relational grade for the experimental mechanical properties are shown in section 2.2, and are similar to the work of Abifarin (2021) and Awodi et al (2021). All the plotted graphs were obtained using Minitab.…”
Section: Taguchi Experimental Designmentioning
confidence: 99%
See 2 more Smart Citations
“…Grey System Theory was established by Professor Deng in 1982, and since then, it has seen its application in a wide range of areas, e.g., healthcare (Aydemir & Sahin, 2019;Quartey-Papafio et al, 2019), environmental sustainability (Shahzad et al, 2020), supply chain (Diba & Xie, 2019;Mahmoudi et al, 2021a;2021b), tourism (Javed et al, 2020a) energy and emissions (Ofosu-Adarkwa et al, 2020;Du et al, 2019;Xie et al, 2020), information systems (Esangbedo et al, 2021), engineering (Abifarin et al, 2021), economics (Camelia, 2015), etc. Also, it has seen applications in project management Mahmoudi et al, 2020; Studies have reported that Grey System Theory based models are particularly useful when data is small or insufficient (Javed et al, 2020b), as is the case in the current study.…”
Section: Grey Absolute Decision Analysis (Gada)mentioning
confidence: 99%